An archivist in turbulent times: the activity of Áurea Javierre in the Library of the University of Zaragoza during the Spanish Civil War (1936- 1939) - Blanco Domingo, Luis (Revista General de Información y Documentación, 2019)
The objective of this article is to analyze the trajectory, accidental and transitory, of ÁureaJavierre in the University Library of Zaragoza; during the Spanish Civil War (1936-1939). Throughvarious documentary sources, a part of the biography of the turolense archivist virtually unknown isreconstructed, centered on her work organizing the Servicio de Lecturas del Soldado and hercollaboration with Javier Lasso de la Vega, Head of Servicio de Archivos, Bibliotecas y Registro dela Propiedad Intelectual, in the adaptation of the Cuerpo Facultativo de Archiveros, Bibliotecarios yArqueólogos to the new administrative structure that arose with the New State.
Keywords: Spanish Civil War; Servicio de Lecturas del Soldado; Áurea Javierre; Cuerpo Facultativo de Cuerpo Facultativo de Archiveros, Bibliotecarios y Arqueólogos; University Library of Zaragoza